ANWAR TRIUMPHS THE ASCENT OF MALAYSIA'S TENTH PRIME MINISTER AGAINTS ALL ODDS - Trowell, Mark (Marshall Cavendish Editions, 2023)
The four years following Anwar Ibrahim's release from prison on 16 May 2018 is as dramatic as it was chaotic. With rare insider insights, this book uncovers the collapse of the Pakatan Harapan coalition, the turmoil after Mahathir's shocking resignation, and the hard decisions made to secure power. It reveals how Anwar's personal triumph over old rivalries, political betrayals by former allies, and sensational moves to make the nation stronger, eventually led to the hung parliament result of GE15 and his appointment as the tenth prime minister of Malaysia. Testament to the strength and perseverance of a nation and its leader, this book is a must-read for anyone interested in the political landscape of Malaysia and the incredible journey of a man who never gave up on his dreams of a better future for his country and its people.